Characterization of trypsin forms from Atlantic cod (Gadus morhua) - Guðrún Birna Jakobsdóttir 1987- (2012)
Trypsins from Atlantic cod (Gadus morhua) are highly active cold-adapted proteases. The purpose of this project was to characterize a benzamidine purified trypsin isolate from Atlantic cod with special emphasis on trypsin Y. Furthermore, the purpose was to compare the kinetic parameters (kcat, KM and kcat/KM) of cod trypsin Y and cod trypsin I towards various chromogenic substrates. The aim was also to compare the ability of cod trypsin and bovine trypsin to degrade native proteins. The results of this study showed that eight trypsins (trypsins 1-8) were present in the isolate based on 2D gel electrophoresis and cation exchange chromatography. Mass spectrometry analysis on trypsins 1-8 identified trypsin 1 as trypsin I, trypsins 2-7 as trypsin X and trypsin 8 as trypsin Y. The catalytic efficiency of trypsin I was found to be higher than that of trypsin Y towards chromogenic substrates at 25°C. The degradation ability of the cod trypsin isolate was 3-12 times higher than that of bovine trypsin depending on the substrate. Trypsín úr Atlantshafsþorski (Gadus morhua) eru mjög virkir, kulda-aðlagaðir próteinasar. Markmið verkefnis var að greina benzamidín hreinsaða trypsín blöndu úr Atlantshafsþorski með sérstakri áherslu á nýstárlegt form trypsíns (trypsín Y). Einnig, var markmið verkefnis að ákvarða og bera saman hraðafræðilega fasta (kcat, KM og kcat/KM) trypsíns I og trypsíns Y gegn mismunandi gerðum smárra litmyndandi hvarfefna. Þá var einnig borin saman geta þorskatrypsíns og nautatrypsíns við niðurbrot á próteinum í virkri myndbyggingu. Niðurstöður verkefnis sýna að 8 trypsín ísóform er að finna í trypsín blöndu út frá tvívíðum gel-rafdrætti og keyrslu á katjóna skilju. Massagreining á trypsínum 1-8 greinir trypsín 1 sem trypsín I, trypsín 2-7 sem trypsín X og trypsín 8 sem trypsín Y. Hvötunargeta trypsín I reyndist hærri en trypsíns Y við 25°C. Niðurbrotsgeta þorskatrypsín blöndu var allt að 12 sinnum hærri (fór eftir próteini) en nautatrypsíns. AVS Rannsóknasjóður í sjávarútvegi